A Preliminary Study on Current Status of Employment Guidance Work of International Students and Improving Strategies in S Province China - Song, Jia; Yunus, Hashimah Mohd (Journal of Ecohumanism, 2024)
With the continuous opening-up to the world and the continuous improvement of the higher education quality, a growing number of international students are choosing Chinese universities for pursuing their further study. At present, China has become the largest destination in Asia and the third largest destination in the world for studying abroad (Miao & Qu, 2022). In addition to the high quality of the educational environment, the ever-growing economic situation and the vast job market have also become one of the most important factors that influence international students to choose to study in China. Around 2017, with the adjustment of relevant national and local policies for the employment of international students, the employment environment for international students in China has become more relaxed and transparent. Meanwhile, more Chinese enterprises have gradually become internationalized and the demand for international talents has also been increasing, thus providing more opportunities for international students to work in China. The gradually favorable employment environment for international students has prompted universities to continuously strengthen, prioritize and improve the employment guidance work for international students. This paper selected one provincial university in S Province, aimed to explore the current situation of international students’ employment management, the challenges they face, the necessity of employment guidance for international students in universities and the suggestions for employment guidance management. Through questionnaire with the international students and the semi-structured interviews with the international students and administrators of international student management to summarize and analyze the challenges faced by the current employment guidance work for international students. Hope the findings of this paper can provide feasible strategic suggestions for the employment guidance management of international students in S Province.